A green facile in situ synthesis and characterization of cerium doped polyanailine (PANI-Ce) nanocomposite - Zakia Khanam; Farook Adam (2015)
PANI is an unique conjugated polymer because of its controllable doping and dedoping properties. The rare earth metal doped PANI composites in nanorange reported to have several potential applications in magnetic divices and catalyses. In the present study cerium doped PANI composite (PANI-Ce) was prepared by green in situ synthesis with water as solvent and mild oxidizing agent, H₂0₂. Spectroscopic studies (FT-IR and UV-Vis) revealed successful polymerization of PANI-Ce. EDX analysis further supported the presence of Ce in polymer matrix with 5.81 weight percentage. TEM results exhibited that the composite, PANI-Ce exist in nanorange with particle size 3-7 nm. Based on previous ﬁnding ﬁnther study is warranted as nanostructured cerium doped polyaniline hold promise for heterogenous catalysis, sensors and magnetic materials.